SYMBIOTIC EXISTENCE OF UK ECONOMICS TERMS AND THEIR TRANSLATION EQUIVALENTS IN CURRENT BULGARIAN ACADEMIC RESEARCH - Zh. Gundasheva; M. Dragandzhikova; K. Katsarova (Trakia Journal of Sciences)
This article explores the processes of adaptation and change in the transfer of foundational UK economics terms to relevant Bulgarian research literature. The study is based on a corpus of lexemes derived from recent publications in Bulgarian economics journals and dissertations and analyzes the specifics of the symbiosis of various Bulgarian translation equivalents with the original lexemes in Anglo-Saxon usage and their relationships. The used methods are interdisciplinary, i.e. ranging from morphological derivations, semantic and grammatical aspects to intercultural interpretations of existent realia and translation phenomena. The corpus and the inferences elicited from our observations can serve as a reference and educational tool for students of economics and users of related terminology.